Looking for the Way Out: The Attribution of Treatment Responsibility among Greek and German Actors in the Eurozone Crisis Debate. Issue 3 (1st September 2020) - Roose, Jochen; Sommer, Moritz; Kousis, Maria
Abstract: In times of crisis, the attribution of responsibility is at the core of public debates. Next to the question of blame, collective interpretations of who should impose remedies are contested. In the Eurozone crisis, Germany was an obvious addressee for this attribution of "treatment responsibility." After years of relative reluctance, Germany had occupied a new role as it strongly pressured for harsh austerity in Greece and other crisis-hit countries. This article explores the public attribution of treatment responsibility among Greek and German actors in the Eurozone crisis debate. Based on a systematic content analysis of German and Greek newspapers as well as Reuters news reports between 2009 to 2016, we find a surprising absence of German actors as attribution addressees in Greece. Despite Germany's dominant role in the Eurozone crisis, Greek actors stress the responsibility of their own government (and that of eu actors) to act upon the crisis. In the German debate, Greek addressees are one category among many in a strongly Europeanized debate.